Adolescents and young adults with rhabdomyosarcoma treated in the European paediatric Soft tissue sarcoma Study Group (EpSSG) protocols: a cohort study. (August 2022) - Ferrari, Andrea; Chisholm, Julia C; Jenney, Meriel; Minard-Colin, Veronique; Orbach, Daniel; Casanova, Michela; Guillen, Gabriela; Glosli, Heidi; van Rijn, Rick R; Schoot, Reineke A; Cameron, Alison L; Rogers, Timothy; et al.
Summary: Background: Adolescent and young adult patients with rhabdomyosarcoma often have poorer outcomes than do children. We aimed to compare the findings of adolescent and young adult patients with children enrolled in two prospective clinical protocols. Methods: This retrospective observational analysis was based on data from the European paediatric Soft tissue sarcoma Study Group (EpSSG) rhabdomyosarcoma 2005 trial (phase 3 randomised trial for localised rhabdomyosarcoma, open from April, 2006, to December, 2016) and the EpSSG MTS 2008 protocol (prospective, observational, single-arm study for metastatic rhabdomyosarcoma, open from June, 2010, to December, 2016), which involved 108 centres from 14 different countries in total. For this analysis, patients were categorised according to their age into children (age 0–14 years) and adolescents and young adults (age 15–21 years). For the analysis of adherence to treatment and toxicity, only patients with high-risk localised rhabdomyosarcoma included in the randomised part of the rhabdomyosarcoma 2005 study were considered. The primary outcome of event-free survival (assessed in all participants) was defined as the time from diagnosis to the first event (eg, tumour progression, relapse) or to the latest follow-up. Secondary outcomes were overall survival, response to chemotherapy, and toxicity. Findings: Our analysis included 1977 patients, 1720 children (median age 4·7 years; IQR 2·6–8·4) and 257 adolescents and young adults (16·6 years; 15·8–18·0). 1719 patients were from the EpSSG rhabdomyosarcoma 2005 study (1523 aged <15 years and 196 aged 15–21 years) and 258 patients were from the EPSSG MTS 2008 study (197 aged <15 years and 61 aged 15–21 years). Adolescent and young adult patients were more likely than were children to have metastatic tumours (61 [23·7%] of 257 vs 197 [11·5%] of 1720; p<0·0001), unfavourable histological subtypes (119 [46·3%] vs 451 [26·2%]; p<0·0001), tumours larger than 5 cm (177 [68·9%] vs 891 [51·8%]; p<0·0001), and regional lymph node involvement (109 [42·4%] vs 339 [19·7%]; p<0·0001). Adolescent and young adult patients had lower 5-year event-free survival (52·6% [95% CI 46·3–58·6] vs 67·8% [65·5–70·0]; p<0·0001) and lower 5-year overall survival (57·1% [50·4–63·1] vs 77·9% [75·8–79·8]; p<0·0001) than did children. The multivariable analysis confirmed the inferior prognosis of patients aged 15–21 years (hazard ratios 1·48 [95% CI 1·20–1·83; p=0·0002] for poorer event-free survival and 1·73 [1·37–2·19; p<0·0001] for poorer overall survival). Modifications of administered chemotherapy occurred in 13 (15·3%) of 85 adolescents and young adults, and in 161 (21·4%) of 754 children. Grade 3–4 haematological toxicity and infection were observed more frequently in children than in adolescent and young adult patients. Interpretation: This study found better outcomes for adolescent and young adult patients than those reported in epidemiological studies (eg, the EUROCARE-5 study reported 5-year overall survival of 39·6% for patients aged 15–19 years in the 2000–07 study period), suggesting that adolescent and young adult patients, at least up to age 21 years, can be treated with intensive paediatric therapies with no major tolerability issues and should be included in paediatric rhabdomyosarcoma trials. However, the inferior outcomes in adolescent and young adult patients compared with those in children, despite receiving similar therapy, suggest that a tailored and intensive treatment strategy might be warranted for these patients. Funding: Fondazione Città della Speranza.